PENGELOLAAN LIMBAH KOTORAN TERNAK DALAM UPAYA PENCEGAHAN PENCEMARAN LINGKUNGAN DI KOTA KOTAMOBAGU - Linggotu, Lidyasanty O.; Paputungan, U.; Polii, B. (Universitas Sam Ratulangi, 2016)
ANIMAL WASTE PRODUCT MANAGEMENT FOR PREVENTION OF ENVIRONMENTAL POLLUTION IN KOTAMOBAGU CITY. The animal wastes from animal farm affect the environmental condition of human settlement, when it was not well managed. The objectives of this study was to evaluate either levels of knowledge, attitude and technical skill had correlated directly or not with their motivation activity in preventing environmental pollution of animal wastes around Kotamobagu city. Variables in this study were referring on the farmer’s standard knowledge (X1), attitude (X2), technical skill (X3) and motivation activity in preventing environmental pollution of animal wastes (Y) around Kotamobagu city using the functions of linear multiple regression, Yi = b0 + b1X1 + b2X2 + b3X3 + ei; where Yi was the-i observation of farmer’s motivation activity in preventing environmental pollution of animal wastes; b0 was intercept; b1, b2 and b3 were regression coefficients, X1 was farmer’s knowledge, X2 farmer’s attitude, X3 was farmer’s technical skill in preventing environmental pollution of animal wastes; and e1 was random error. Results of this study showed that knowledge level (X1), attitude (X2) and technical skill (X3) of farmers could be the important factors affecting farmer’s motivation activity in preventing environmental pollution of animal wastes (Y) in Kotamobagu city areas. The equation of multiple regression model was found, Y = 1.468 + 0.784 X1 + 0.218 X2 + 0.004 X3. The determination coefficient (R2) of 0.81 in this model indicated that 81 percents of the variation of independent variables (X1, X2, and X3) used in the model were able to affect the variation of the dependent variable (Y). The rest of 19 percents in the model were caused by the other unknown factors. The average score values of knowledge level (X1=87.23), attitude (X2=93.37) and technical skill (X3=88.40) and farmer’s motivation activity (Y=90.60) in preventing environmental pollution of animal wastes (poultry and pig) in Kotamobagu city areas were still below the score median values (X1=93; X2=100; X3=100; Y=93) of those variables. This condition suggested that extension activities related to the prevention of environmental pollution of animal wastes in Kotamobagu city areas were still needed to be conducted, mainly to the farmers with low scores in knowledge, attitude, technical skill and motivation activity in preventing environmental pollution of animal wastes. Key words: Animal waste product, prevention of environmental pollution, Kotamobagu city.